Mastering Reading: Elevating Tenth Grade Comprehension with Quizizz at Senior High School - Wahyuningsih, Sri; Jaya, Wayan Satria; Vinantiastuti, Maria Lovelita (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
The study was aimed to increase students’ reading comprehension through Quizizz Application Strategy at the tenth grade of SMA Taman Siswa Teluk Betung Bandar Lampung, In academic year 2023-2024. The participants of the research were the researcher as a teacher, the English teacher collaborated as observer and the students of class X E- 2. The subjects of research were 34 students which consisted of 19 female and 15 male. In this research, the researcher used classroom action research design consisting of two cycle.The data was collected through observation sheet, and test. The research was focused to increase students' learning activities and students' reading comprehension. The improvement of students' learning activities showed mean score of students' learning activities in cycle I was 6,17 with the criteria was less active. While, the mean score of students' learning activities in cycle II was 7,26 with the criteria was quite active. The improvement of students' reading comprehension showed mean score in cycle I was 68,88, there were 19 students who achieved score above Minimum Mastery Criteria or 55,88%, and the mean score of cycle II was 79,26, there were 27 students who achieved score above Minimum Mastery Criteria or 76,97%. So, the improvement of students’ reading comprehension in cycle I to the cycle II was 0,25 point. From analyzing data, it could be concluded Classroom Action Research by conducting Quizizz Application Strategy Improved students' learning activities and students' reading comprehension.